An Analysis on the Tendency of Pronunciation Made by Students with Indonesian Linguistic Background - Ranni Putri Stefani; Ahmad Roba’i (TEKNOSASTIK, 2018)
The compulsory of speaking English to communicate at campus environment made the writers interested in the tendency of English pronunciation made by English students with Indonesian linguistic background. The question appeared was what kinds of difficulties that the learners face when they pronounce English words or when they speak in English. The objective was to find out the tendency of the mistakes they make. The data were collected by conducting direct observation in and outside classes. The talks or presentations made by the students were recorded. From the observation, the writers listed mispronounced words. The writers then used the words in written sentences and asked students to read those sentences. The students were also interviewed in order to have another measurement to determine the tendency occurring in the data. As results, most of the mispronunciation problems found were related to vowels, consonants and word stress. These are the most noticeable findings among other issues discovered after conducting the research.Key Words: English, foreign language, mispronunciation, phonetics, phonology